Genomic Analysis of Microbulbifer sp. Strain A4B-17 and the Characterization of Its Metabolic Pathways for 4-Hydroxybenzoic Acid Synthesis - Tian, Jun; Zhu, Li; Wang, Wenjun; Zhang, Liping; Li, Zhi; Zhao, Qingyu; Xing, Ke; Feng, Zhaozhong; Peng, Xue (Frontiers in Microbiology, 2018)
The marine bacterium Microbulbifer sp. A4B-17 produces secondary metabolites such as 4-hydroxybenzoic acid (4HBA) and esters of 4HBA (parabens). 4HBA is a useful material in the synthesis of the liquid crystal. Parabens are man-made compounds that have been extensively used since the 1920s in the cosmetic, pharmaceutical, and food industries for their effective antimicrobial activity. In this study, we completed the sequencing and annotation of the A4B-17 strain genome and found all genes using glucose for the 4HBA biosynthesis. Strain A4B-17 uses the EMP, HMP, and ED pathways to utilize glucose. Other sugars such as fructose, sucrose, xylose, arabinose, galactose, mannitol, and glycerol supported cell growth and 4HBA synthesis. Reverse transcriptional analysis confirmed that the key genes involved in the glucose metabolism were functional. Paraben concentrations were proportionally increased by adding alcohols to the culture medium, indicating that strain A4B-17 synthesizes the 4HBA and the alcohols separately and an esterification reaction between them is responsible for the paraben synthesis. A gene that codes for a carboxylesterase was proposed to catalyze this reaction. The temperature and NaCl concentration for optimal growth were determined to be 35 °C and 22.8 g/L.